RESEÑA de : Bastida Frejeido, Francisco; Villaverde Menéndez, Ignacio; Requejo Rodríguez, Paloma; Presno Linera, Miguel Ángel; Aláez Corral, Benito; Fernández Sarasola, Ignacio. Teoría general de los derechos fundamentales en la Constitución Española de 1 - Presno Linera, Miguel Ángel (Teoría y Realidad Constitucional, 2005)
-